Benefits of adopting seed-based technologies for rehabilitation in the mining sector: A Pilbara perspective - Erickson, T.; Muñoz-Rojas, M.; Kildisheva, O.; Stokes, B.; White, S.; Heyes, J.; Dalziell, Emma; Lewandrowski, W.; James, J.; Madsen, M.; Turner, S.; Merritt, D. (CSIRO Publishing, 2017)
© 2017 CSIRO. All rights reserved. The use of native plant seeds is fundamental to large-scale rehabilitation and the re-establishment of self-sustaining ecosystems after high-impact mining activity has ceased. However, many of the biological attributes of seeds are often overlooked in large-scale rehabilitation programs. Multi-disciplinary, long-Term research collaborations are required to improve seed-based mine rehabilitation. In this paper, we review the steps that BHP Western Australia Iron Ore (WAIO), a large iron ore mining company that operates in the Pilbara bioregion of north-west Western Australia, has taken over the past 9 years to ensure continuous improvement in rehabilitation procedures. We introduce the mining activities that WAIO undertake in the Pilbara, and emphasise specific examples of how research findings have led to incremental improvements in the seed management cycle, growth media management and mine rehabilitation practices. Specifically, we outline how the implementation of structured seed collection and storage programs has created the capacity to maintain high-quality seed stocks sufficient for 3-5 years of future rehabilitation. Research has documented the prevalence of seed dormancy in the flora ( > 70% of 105 species examined produce dormant seeds), with physical and physiological classes of dormancy most commonly encountered. We discuss the development of seed-Treatments such as optimised wet-heat and dry after-ripening that have increased the germination capacity of many previously dormant seed batches. In addition, we highlight how seed enhancement technologies, such as hydro-priming with smoke-derived germination stimulants and polymer seed coating, and a greater understanding of the biological and physical limitations present in the growing environment, have vastly improved seedling emergence performance under field conditions for key framework Triodia species. Ongoing industry support (e.g. construction of a purpose-built rain manipulation shelter) has ensured research in the Pilbara will continue to unpack and resolve the complex challenges associated with seed regeneration of biodiverse native plant communities after mining.